Case Report: Report of Infective Endocarditis Caused by Abiotrophia defectiva and Literature Review - Du, Yanqiang; Zhang, Zhan; Chen, Chao; Xia, Han; Zhang, Hua; Guo, Zhangyan; Wang, Yi (Frontiers in Pediatrics, 2022)
Objective To report the clinical characteristics of the first child with infective endocarditis (IE) caused by Abiotrophia defectiva in mainland China and to improve the understanding of the disease. Methods The clinical data of a child with IE caused by A. defectiva admitted to Xi'an Children's Hospital in July 2021 were collected, and relevant literature was reviewed. Results The child, female, aged 8 years, was admitted due to fever for 4 days and right limb hemiplegia for 3 days. The disease started with suppurative tonsillitis, followed by headache, fatigue, right-sided mouth, slurred speech, right limb weakness, and unstable holding. Echocardiography showed mitral valve neoplasm vegetation formation and vegetation formation at the entrance of the pulmonary vein in the lateral posterior wall of the left atrium. Cranial contrast-enhanced magnetic resonance imaging (MRI) + magnetic resonance angiography (MRA) showed multiple intracranial pseudoaneurysm formation and pontine infarction. Metagenomic next generation sequencing (mNGS) of cerebrospinal fluid and blood detected A. defectiva. Anti-infective treatment with meropenem in combination with vancomycin was given. On the 36th day after admission, the child developed severe headache and slurred speech. A head CT was completed, which showed a right parietal pseudoaneurysm hemorrhage and cerebral sickle hernia. She was then immediately given a right temporo-occipital hematoma evacuation, cerebrovascular malformation resection, and decompressive craniectomy. After the surgery, her speech ability gradually recovered, and the muscle strength of her left upper limb was about grade III, while the muscle strength of the rest of the limbs was normal. After hospitalization for a total of 60 days, her family requested to be discharged. Conclusion This child patient is the first case of childhood IE caused by A. defectiva in mainland China, and the first time in the world that A. defectiva was detected by mNGS in a IE patient.